The efficacy of a multicomponent functional fitness program based on exergaming on cognitive functioning of healthy older adults: a randomized controlled trial - Gouveia, Élvio R. (2021)
Background and Objectives: Regular physical exercise can attenuate age-related cognitive decline. This study aimed to investigate the effect of a physical exercise multicomponent training based on exergames on cognitive functioning (CF) in older adults. Research Design and Methods: This randomized controlled trial included older adults aged 61–78. Participants were randomly allocated to an intervention group (IG; n = 15) or active control group (CG; n = 16). The IG was exposed to a combined training with traditional exercise and exergaming, twice a week over a period of 12 weeks. The CG performed only traditional sessions. CF was assessed by the Cognitive Telephone Screening Instrument. The time points for assessment were at zero (pretest), 12 (posttest), and 17 weeks (follow-up). Results: Active CG and IG increased from pretest to posttest in short-term memory (STM), long-term memory (LTM), and Cognitive Telephone Screening Instrument total score 1.98 > Z < 3.00, ps < .005, with moderately large positive effects (.36 > r < .54). A significant increase was seen from posttest to follow-up in STM, Z = 2.74, p = .006, and LTM, Z = 2.31, p < .021, only in IG. Across the two time periods posttest to follow-up, there were significant interaction effects between program type and time for STM (p = .022, η2 p = .17) and LTM (p = .004, η2 p = .25), demonstrating a more beneficial effect of the exergames intervention compared to the CG. Discussion and Implications: The integration of exergaming in a multicomponent functional fitness exercise might have the potential to maintain and improve CF (in particular, STM and LTM) in older adults.